THE INFLUENCE OF GUIDED QUANTUM MODEL APPLICATION TOWARD SOCIAL STUDIES ACHIEVEMENT REVIEWED FROM THE PARTICIPATION ON THE FOURTH GRADE STUDENTS SDN 2 SOKARAJA TENGAH - Elsa Okti Inkamawarni; Pamujo Pamujo; Sri Harmianto (Universitas Muhammadiyah Purwokerto, 2014)
The purposes of this study were: 1) know the influence from the guided quantum model toward sosial studies achievement, 2) know the influence of the participation toward the sosial studies achievement, 3) the interaction using the guided quantum model, direct learning model and student’s participation toward the sosial studies achievement. This type of research is experimental research. The sampling that used in this research is the cluster random sampling technique. The population were the fourth grade students of SDN 2 Sokaraja Tengah that consist of two class, there’s IV A class as the experiment class and the IV B class as the control class. The sampling in the IV A class using the guided quantum model and the IV B class using direct learning model. The sampling is used a test and questionnaire. The data analysis is used two lane variance analysis. The result showed that, 1) the guided quantum model has an influence to student’s sosial studies achievement that proved with Fcolumn = 4,698> Ftable = 4,02significance column 0,048 Ftable = 4,02 significance line 0,030< 0,05, 3) there’s no interaction between guided quantum model, direct learning and students participation toward sosial studies achievement that proved Finteraction = 0,828< Ftable = 4,02 interaction significance0,166> 0,05.